Vegetation Patchy Dieback: A Case Study of Colophospermum mopane Vegetation Type in Semi-arid Botswana - Shimane W. Makhabu; Rabson Nthata (Research Aspects in Biological Science Vol. 2, 2022)
Patch dieback of Colophospermum mopane (Kirk ex Benth.) Kirk ex J. Léonard, has been reported in South Africa and has been attributed to drought, soil surface condition and soil chemistry. In east Africa dieback of Vachellia xanthophloea (Benth.) P. J. H. Hurter, synonyms Acacia xanthophloea Benth has been reported and has been attributed to both raised ground water table and increased soil salinity following a period of higher rainfall. In 2012, dieback of C. mopane and other species was discovered in Botswana’s north-eastern region (North West of Francistown). The causes of the dieback that had been noticed were unknown. The goal of this research was to determine the status and causes of that dieback. Specific objectives for this study were to determine the woody species composition in the area, species with dieback, percentage number of individuals of each species with dieback, what people in the area think were the causes of the dieback and whether rainfall, temperature and soil type affect the dieback. The study was based on field survey to determine species with dieback, the relative composition of the species affected and the areas affected. A questionnaire was also administered to get views from residents of the areas on what they thought caused the dieback. Rainfall and temperature data were obtained from Department of Meteorological Services. It was found that it was not only C. mopane affected but even other species. It was found that it was not only C. mopane affected but even other species such as Dichrostachys cinerea, Combretum hereroense and Terminalia prunioides. There was amble evidence that low temperature combined with soil type appeared to have been the major causes of the dieback. Dieback of the trees was on heavy clay soils than on loamy soils. Finding of the study appears to suggest that dwarf C. mopane on heavy clay soils patches might be the result of occasional occurrence of diebacks.